An integrated approch to water management in Kayseri : rain water collection and storage design for Kayseri Harıkalar Dıyarı water-ski park - Karakoçak, B. Begüm. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2011., 2011)
Water management in metropolitan areas in developing countries is a major environmental challenge of the future. Turkey‟s position for increased regional leadership on water issues is gaining acceptance through developing regions of Central Asia, Middle East and Africa. Concepts and technologies about integration and vision must be implemented to gain broader acceptance and relevance. Within this study; current water and wastewater management systems are investigated for Kayseri, with the purpose of bringing water into the center of city life by a reformed proposed pilot project. In this study, ways of utilizing water as a central feature of Kayseri urban design within the frame of the IWA Cities of the Future Project was investigated. A water-ski park was designed, located in a recreational area called the Kayseri Harikalar Diyarı. Water in the park was rain and storm water collected in tanks and circulated continuously. In order to both assess the quantity and dynamics of water flow through the Kayseri Harikalar Diyarı Water-Ski Park, Environmental Protection Agency‟s (EPA) Storm Water Management Model (SWMM) was used. The evaporation rates, temperature and snow melt data were introduced to the model as input parameters. The model simulated the water quantity and response to the events that will occur continuously for a 3-year rainfall record. Simulations were conducted in the EPA SWMM 5.0 to assess a proposed triangular open channel with a length of 2147 m and a slope of 0.3%. Two underground storage tanks, each with a volume of 50m3 were designed for storm/rain water collection. The obtained results demonstrated that after three years, 38,300 m3 rain water could be stored in the two proposed underground storage tanks. 43% of the water-ski lake with a volume of 90,000m3, could be recharged with the stored rain water. According to World Health Organization (WHO) guidelines for water reuse for different purposes of water and EU Directive for Bathing Water (2006/7/EC), the rain water analyses conducted in KASKI laboratories showed that the rainwater quality objectives met requirements for use for both irrigation and bathing water purposes.
Keywords: Water quality management -- Turkey -- Kayseri.; Water quality management -- Mathematical models.